2019
DOI: 10.1159/000499691
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mixed Hepatitis C Virus Genotype Infection and Its Effect on the Response to Direct-Acting Antivirals Therapy

Abstract: Background: The incidence of mixed hepatitis C virus (HCV) genotype infection is variable, and a few reports exist regarding the efficacy of direct-acting antivirals (DAA) therapy for mixed genotype. We aimed to investigate the prevalence of mixed genotype and its impact on the virologic response to DAA therapy. Methods: A total of 365 patients with chronic HCV infection who completed antiviral therapy were recruited. Nested polymerase chain reaction with universal and specific primers of genotypes 1b and 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is well recognized that mixed genotype is more common in patients with repeated HCV exposures [15,16]. Recently, patients with mixed infection were paid more concern with the development of detection methods [15,17,18]. Di erent patterns of mixed infection had been reported in China, such as 1b/2a, 1b-2k, 6a/2a, 6a/1a, 1b-2k, 3-6, and so on, of which the most common in China was 1b/2a [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that mixed genotype is more common in patients with repeated HCV exposures [15,16]. Recently, patients with mixed infection were paid more concern with the development of detection methods [15,17,18]. Di erent patterns of mixed infection had been reported in China, such as 1b/2a, 1b-2k, 6a/2a, 6a/1a, 1b-2k, 3-6, and so on, of which the most common in China was 1b/2a [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate detection of mixed HCV infections is crucial for effective clinical diagnosis 25 . Our study demonstrated that both assays generally can effectively confirm mixed HCV infections when the minor genotypes exceeded approximately 8.4% of the viral load.…”
Section: Discussionmentioning
confidence: 73%
“…Genotype 3 was commonly found in drug abusers. Determination of HCV genotype requires the use of PCR to hybridize to genotype-specific probe that allows understanding route of HCV infection of the patient and helps clinicians to determine the duration of interferon therapy [ 2 , 6 ] or choosing genotype-specific DAA therapy before the introduction of current pan-genotypic DAA therapy [ 14 , 18 , 19 , 32 ]. However, less than ten percent of the patients were infected with the mixed variant of the HCV, especially those infected with HIV or intravenous drugs users [ 17 , 21 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2020 EASL [ 14 ] and 2019 AASLD [ 15 , 16 ] treatment guidelines now suggest two main regimens for treatment-naïve patients, i.e., glecaprevir (300 mg)/pibrentasvir (120 mg) (GLE/PIB), and sofosbuvir (400 mg)/velpatasvir (100 mg) (SOF/VEL) with pan-genotypic antiviral activity to simplify the treatment algorithm. A minority of the patients may get infected with a mixed HCV genotype [ 17 , 18 , 19 ] or the HCV genotype that was undetermined by conventional polymerase chain reaction (PCR) techniques [ 20 , 21 ]. To date, there is a paucity of real-world data on the effectiveness and safety of pan-genotypic DAAs for patients with these two specific scenarios for HCV elimination [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation